COVID-19 Restrictions in a Nature Reserve Reveal the Costs of Human Presence for the Threatened Nubian Ibex (Capra nubiana) - Zukerman, Yuval; Sigal, Zehava; Berger-Tal, Oded (Frontiers in Ecology and Evolution, 2021)
The increasing pressure of ecotourism on wildlife in their natural habitats has led many wild animals to alter their behaviors. The restrictions that were issued in many places due to COVID-19 provide a rare opportunity to examine wildlife behavior in nature reserves with reduced human presence, and elucidate the impact of human visitation on the behaviors and fitness of local wildlife species. In 2019 and 2020 we placed trail cameras next to two natural springs in the Israeli Negev Desert, Ein-Avdat and Ein-Shaviv, located 9 km apart. Both sites serve as the main water source for local Nubian ibex (Capra nubiana) populations, but Ein-Avdat is situated within a popular national park into which visitors' entrance was restricted due to COVID-19 regulations in 2020, while Ein-Shaviv is more remote and thus attracts only few visitors regardless of COVID-19 regulations. Our study revealed that during 2020, ibex in Ein-Avdat arrived to drink earlier in the day and the population's kids-to-females ratio had more than doubled. These changes were not observed in Ein-Shaviv. We found that the daily number of visitors in Ein-Avdat affect the arrival time of ibex to the water pool. We conclude that the reduced number of visitors to Ein-Avdat in 2020 compared to 2019 may have allowed the ibex to arrive in preferred hours, and can be the reason for the increased kid-to-females ratio. Our study shows that behavioral adaptions to human visitation in nature reserves might carry a high fitness cost.